Public School Board Presidents' and Superintendents' Perceptions of the Characteristics of Effective Superintendents in a Midwestern State. Issue 6 (November 2017) - Webner, Steven; De Jong, David; Campoli, Ayana; Baron, Mark
The expectation for strong superintendent leadership has increased due to a demand for greater student achievement and accountability. This study examined public school board presidents' and superintendents' perceptions of the characteristics superintendents must possess to effectively lead in today's complex educational system. A researcher-developed survey instrument was used to collect data from public school board presidents and superintendents in a Midwestern state. Computation of item means indicated school board presidents perceived developing a close, positive, and productive relationship with the school board, developing a culture and climate which enhances teacher morale and student achievement, developing partnerships between school and community, developing budgets and manage fiscal matters, and visibility throughout the community and district as the most important characteristics of effective superintendents. Superintendents perceived developing a culture and climate which enhances teacher morale and student achievement, developing a close positive, and productive relationship with the school board, building a team atmosphere and coherence, developing budgets and manage fiscal matters, and communicating with stakeholders as the most important characteristics of effective superintendents. School board presidents considered involvement of stakeholders in collaborative goal-setting and monitoring as well as superintendent visibility throughout the community and district to be significantly more important than did superintendents. In contrast, superintendents believed recruiting, selecting, developing personnel, and implementing effective evaluation structures to be significantly more important than did the superintendents. Independent sample t tests revealed that small district public school superintendents perceived recruiting, selecting, developing personnel, and implementing effective evaluation structures as significantly more important than small district school board presidents did ( p < .05). There was no statistically significant difference in perceptions for the 20 characteristics of effective superintendents between large district board presidents and superintendents, or between less experienced school board presidents and superintendents ( p < .05). More experienced school board members perceived involving stakeholders in collaborative goal-setting and monitoring to be statistically significantly more important than did more experienced superintendents ( p < .05).